The Manila Public School Teachers Association a case study - Mendoza, Maria Erlinda (Ilagan) 1933- (1974)
The Manila Public School Teachers Association was founded in 1947 to upgrade the teaching profession and promote the welfare of its members. Its membership has become so vast that the happiness and contentment of the members have become a tremendous goal for the association. The members think that the association has done more than enough to disseminate vital information and issues through an official organ and other communication media and to encourage teachers to exercise their rights and privileges as citizens. The members think the association has done only more than little to encourage higher qualifications for entrance into the teaching profession.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Manila Public School Teachers Association; Educational associations -- Philippines